IDENTIFICATION DES CAUSES DE L’INSECURITE DANS LE PARC NATIONAL DES VIRUNGA EN TERRITOIRE DE NYIRAGONGO - Master ENOCK AMANI ALYCIEN, (IJRDO - Journal of Social Science and Humanities Research, 2024)
Insecurity being the lack of peace of mind, but also the absence of a situation where one findoneself in the state of seeing that no danger is to be feared, this phenomenon in the worldcontinues to manifest itself in protected areas as in national parks and this affects the localpopulations who encounter several difficulties of all kinds.Insecurity everywhere as in national parks does not come from chance but is due to severalfactors, this study is part of the identification of the causes of insecurity in the VirungaNational Park in Nyiragongo territory found in the province of North Kivu in the DemocraticRepublic of Congo. It notes the fact that natural resources are victims of external events thatdamage their development. The observation is that the Virunga National Park is a victim ofinsecurity manifesting itself on a large scale and has repercussions on the populations living inthe Nyiragongo territory, particularly those of the Kibumba group, our target for the surveys.The focus group discussion, descriptive methods, face-to-face interview methods are methodsthat have been used to arrive at the point of finding the results in the data collection accordingto the assessments of the respondents.After the data collection work, it was noticed that conflicts between farmers and unemploymentare major factors that cause large-scale insecurity in this park according the populationssurveyed while signifying that the causes are numerousBeyong these two major causes, poverty, poor governance, conflicts over arable land, the nonintegration of local populations into the hierarchical staff of park management, and theignorance of the population are other factors that are the source of insecurity in the VirungaNational Park.